INTERDISCIPLINARY CONTEXT OF MASTER - FUTURE TEACHER-PHILOLOGIST PEDAGOGICAL TRAINING UNDER THE RAPID DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES - T. Koval (Borys Grinchenko Kyiv Metropolitan University, 2017)
The article deals with the analysis of the scientific and methodological works on the complex characteristics of the category of interdisciplinarity. The features of the educational process of Masters - future teachersphilologists in the context of interdisciplinary, technological competence and approaches are investigated. Theoretical aspects of the concept of "ICT competence of a teacher-philologist" as an integrative quality of the individual that determine its preparedness and ability to use in educational activities of information and communication technologies to satisfy their individual needs and the formation of general and professional (language and speech) competencies in learning foreign languages are the problems of our research. Arrangement of interdisciplinary research of multimedia electronic educational resources in the process of the Masters - future teachers-philologists training requires certain organizational and pedagogical conditions such as: formation of a certain level of general and professional (subject) competencies, including the development of ICT competence and interdisciplinary vision of their future professional activity in the direction of technologizing; implementation into the content of Masters teacher training such modules as "The Use of Educational ICT Technologies in Teaching Foreign Languages", "Actual Problems of High School Pedagogy in Conditions of Education Informatization", "Еlectronic Multimedia Educational Resources as Objects of Interdisciplinary Research"; the use of methods of study on the feasibility of creating and using multimedia electronic educational resources in the educational activity - electronic teaching systems, multimedia electronic textbooks, case studies, teaching materials in distance learning systems such as Moodle. The author emphasized the necessity for arrangement for interdisciplinary research on multimedia electronic educational resources in foreign languages teaching in the process of Masters pedagogical training according to the professional, methodological, psychological, didactic, technologically programmed and statistical requirements.